If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + 11 = 0 Reorder the terms: 11 + 12n = 0 Solving 11 + 12n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 12n = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 12n = 0 + -11 12n = 0 + -11 Combine like terms: 0 + -11 = -11 12n = -11 Divide each side by '12'. n = -0.9166666667 Simplifying n = -0.9166666667
| x-(90+0.3x)=0.2x | | Y=1.2x+5 | | 1+2x=2x | | 12z=25 | | 2x^2+3x+4xy+6y=0 | | 4(5x+3)=x+2 | | 5y=47 | | 3(5x+3)=x+2 | | 4(u+6)=-2(5u-7)+6u | | 3(5x+2)=x+3 | | 70.00+x=74.30 | | 3x+7=10y | | x^3-3x^2-16x-12=0 | | 3[3-(-6x-7)]=90x+114 | | x+83= | | 2(x-4.40)=6.60 | | 3(t+1)=5(2t-5) | | 3x^2+3y^2-15x-30y=0 | | (2x^2-7)(8x^2+3)= | | 4y-16+8y=-4y | | 7(5x+2)=x+3 | | 4w+8= | | 4mn+3m+8n+6= | | 5w+5= | | 8x+9-4(x+1)=9x+7 | | 3p+80=-2p | | 3640=P(l+0.06*5) | | 8Y+9X=73.50 | | (3x+8)(6+x)=0 | | 4(3t+1)-7=t-(t+2) | | m-17/5-7m-7/4=3 | | 6-6(3x-4)=12 |